TEACHERS’ STRATEGIES IN IMPLEMENTING FORMATIVE ASSESSMENT IN ENGLISH LANGUAGE TEACHING - Riska Yulistiana (Journal of English Education Program (JEEP), 2014)
This study is concerned with the issues of formative assessment strategies in English language teaching. Formative assessment has essential role in promoting students’ learning to gain better achievement. It was aimed to know teachers’ strategies in implementing formative assessment and to describe how teachers implemented each strategy in English language teaching. A case study methodology was employed in this research, and the data were collected through classroom observation and interview. The participants of the study consist of two teachers from one of state high school in Ciamis. The data gained was analyzed by using framework of formative assessment strategies proposed by Leahy et al. (2005). The finding revealed that the five strategies of formative assessment were implemented by the English teachers. In addition, there were a variety of ways in its implementation related to the class need. The teachers adjusted to findings information about students’ learning situation as well as an available instructional time. Based on these findings, it is recommended that teachers have to concern about formative assessment in English language teaching. The teachers should be able to implement strategies of formative assessment which is adjusted to the characteristic of students and instructional findings.Key words: Teacher, Strategies, Formative Assessment